DDM1 Controls Heritable Natural Epigenetic Variation in Arabidopsis - Peng Zhang; Datong Xing; Muhammad Shahbaz Chishti; Linan Xie; Qingzhu Zhang (Molecular Ecology, 2025)
As a part of epigenetic modifications, DNA methylation involves the addition of a methyl group to cytosine. In plants, this process occurs in three sequence contexts (CG, CHG and CHH) through two pathways: de novo DNA methylation and DNA methylation maintenance. DNA methylation is highly conserved between ecotypes due to its heritability and role in genomic stability. However, numerous naturally occurring differentially methylated regions (NMRs) exist between ecotypes, which are also heritable and contribute to differential gene expression and phenotypic variation. Decreased DNA methylation observed in mutants of RdDM or DNA methylation maintenance pathways highlights the potential roles of these pathways in NMR formation and inheritance. Nevertheless, the complexity of plant DNA methylation across different contexts and pathways has made the contributions of these two pathways in NMR formation and inheritance remain unclear. To address this, we chose two Arabidopsis thaliana ecotypes, Col‐0 (Col) and C24, and utilised mutants of pol4/5 and ddm1 in both ecotypes. By examining the changes in NMRs within these mutants, we aimed to elucidate the roles of DNA methylation pathways in NMR formation and inheritance. Our results revealed (1) NMRs can be categorised into three types, but classification is not solely based on methylation contexts; (2) compared to RdDM, the DNA methylation maintenance pathway plays a more dominant role in NMR formation and is less influenced by SNPs; (3) DNA methylation maintenance, rather than RdDM, controls NMR inheritance. Our findings highlight the role of the DNA methylation maintenance pathway in NMR formation and inheritance.

Downregulation of galectin-3 by EGF mediates the apoptosis of HepG2 cells - Zhenzhen Hu; Xiuqin Jiang; Ying Xu; Nan Lu; Weizhi Wang; Jie Luo; Han Zou; Datong Zheng; Xing Feng (Molecular and Cellular Biochemistry, 2012)